2006
DOI: 10.1021/jf060520z
|View full text |Cite
|
Sign up to set email alerts
|

Lipophilic Hydroxytyrosyl Esters. Antioxidant Activity in Lipid Matrices and Biological Systems

Abstract: Antioxidant activities of lipophilic hydroxytyrosyl acetate, palmitate, oleate, and linoleate were compared with those of hydroxytyrosol, alpha-tocopherol, and butylhydroxytoluene (BHT) in both glyceridic matrix and biological systems. Aliquots of a glyceridic matrix spiked with various concentrations of antioxidant were subjected to accelerated oxidation in a Rancimat apparatus operated at 90 degrees C. The relationships between induction time (IT) and antioxidant concentration (mmol/kg) presented by hydroxyt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
121
0

Year Published

2007
2007
2015
2015

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 118 publications
(128 citation statements)
references
References 43 publications
7
121
0
Order By: Relevance
“…However, as a general guide to their potency, oleuropein and hydroxytyrosol have been shown to be more effective than vitamin E [108] and butylated hydroxytoluene (BHT) or other synthetic antioxidants approved for use in foods [109][110][111].…”
Section: Phenols As Related To Oxidative Stability Of Voomentioning
confidence: 99%
“…However, as a general guide to their potency, oleuropein and hydroxytyrosol have been shown to be more effective than vitamin E [108] and butylated hydroxytoluene (BHT) or other synthetic antioxidants approved for use in foods [109][110][111].…”
Section: Phenols As Related To Oxidative Stability Of Voomentioning
confidence: 99%
“…In this direction, a recent trend is the synthesis of compounds based on efficient natural antioxidants. Characteristic examples are those derived from hydroxytyrosol (HT) (Manna, Migliardi, Sannino, De Martino, & Capasso, 2005;Trujillo et al, 2006), a phenol found in the polar fraction of olive oil for which, including other related olive oil phenols, a health claim has been officially established (Commission Regulation (EC) No 432/2012). Among these derivatives, isochroman ones recently synthesized (Mateos et al, 2015) seem promising taking into account that except for the modification of HT polarity -main target of past attempts -functional moieties including e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Synthesis of hydroxytyrosyl acetate via benzylation of phenolic hydroxyls A two-step procedure involving the reaction of methyl orthoformate-protected hydroxytyrosol with acetyl chloride, and hydrolytic deprotection in phosphate buffer under very mild conditions (pH=7.2) to get hydroxytyrosyl acetate (87% overall yield) (Scheme 3) was also described as a successful procedure for the preparation of HT-derived esters (Gambacorta et al, 2007 In order to overcome the problems associated to the protection and deprotection steps of the phenolic hydroxyl groups, different methods for the preparation of hydroxytyrosyl esters by reaction of hydroxytyrosol with various acylating agents have been described, such as esterification with free acids (Appendino et al, 2002), transesterification with methyl or ethyl esters (Alcudia et al, 2004;Trujillo et al, 2006), acyl chlorides (Torregiani et al, 2005) and the use of enzymatic methodologies (Grasso et al, 2007;Mateos et al, 2008;Torres de Pinedo et al, 2005;Buisman, 1998).…”
Section: Protection Of Phenolic Hydroxyl Groupsmentioning
confidence: 99%
“…HT transesterification using methyl or ethyl esters and p-toluenesulfonic acid as catalyst has been described as a method without the need of protection of the aromatic hydroxyl groups due to its total chemoselectivity (Alcudia et al, 2004;Trujillo et al, 2006). This method involves heating a solution solution of hydroxytyrosol in the corresponding ethyl or methyl ester, containing a catalytic amount of p-toluenesulfonic acid (Scheme 4).…”
Section: Acid Catalyzed Transesterificationmentioning
confidence: 99%
See 1 more Smart Citation